From the Laboratory to Digital Reality: A Systematic Review of Neuromarketing Applications in Understanding Consumer Experience in Digital Environments - Korošec, Leon; Leskovar, Robert (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
In this article, systematically review is presented and critically evaluated neuromarketing research published between 2020 and 2025 that examines consumer experience in digital environments. Building on a systematic qualitative literature review, the studies employing EEG, eye-tracking, galvanic skin response, and facial expression analysis in the context of websites, e-commerce, digital advertising, and virtual reality are analysed. Conceptual framework grounded in the triad attention-emotion-decision to explain how visual attention, emotional engagement, and decision-making processes jointly shape digital user experience is explored. Findings indicate a clear shift from laboratory-based experiments toward studies conducted in ecologically valid digital settings, alongside a growing importance of multimodal, AI-supported approaches to content personalization. In conclusion, key methodological and ethical challenges are identified and directions for future research and practical application of neuromarketing in digital marketing are outlined.